Integridade da mucosa esofágica na doença do refluxo gastroesofagico: proteção do polisacarideo sulfatado da gracilaria caudata - Sales, Thiago Meneses Araújo Leite (2018)
Gastroesophageal reflux disease (GERD) has a high global prevalence and impact on quality of life. However, patients with GERD have differences in esophageal mucosa integrity and do not respond well to treatment with proton pump inhibitors (PPIs). Thus, the present study aims to characterize the integrity of esophageal mucosa in GERD phenotypes and to investigate the effect of protection with sulfated polysaccharide from Gracilaria caudata (PGC). A consent form was applied, followed by a standardized questionnaire for patients with GERD. Six esophageal biopsies were collected and assembled in Ussing chambers and the basal transepithelial electrical resistance (RET) was evaluated. PGC was applied topically (0.1, 0.3 and 1%) followed by exposure with acid solution (pH 2.0) containing pepsin and taurodeoxycholic acid (TDCA) for 30 min, where RET was continuously measured. Control biopsies were submitted to the acidic solution only. The acid solution was then replaced with fluorescein solution for permeability evaluation. A total of 37 patients with GERD, categorized in patients without erosion (PSE) (n = 19) and patients with erosive esophagitis (PEE) (n = 18), with predominance of females (F / M-24/13). Compared to PSE, PEE presented higher frequency of heartburn and use of PPIs, but significantly lower baseline RET (114.4 ± 5.4 and 163.2 ± 8.19 Ω / cm2, respectively; P <0.01). The acidic solution promoted a gradual decrease in RET of PSE and PEE (27.21 ± 2.4 and 19.92 ± 1.7% drop, respectively; P <0.01), and similar RET at the end of 30 min (PSE: 77 [26-218] versus PEE: 91.5 [43-263] Ω / cm 2, P = 0.20). There was no significant difference (P = 0.30) in the permeability after exposure with acid solution (PSE: 194.4 ± 40.2 and PEE: 222.8 ± 62.9 Tn / To). On the other side, the topical application of PGC significantly prevented (P <0.001) and in a concentration-dependent manner, with maximum effect at 1% concentration, changes in RET in PSE (4.06 ± 4.08 fall), but not in PEE (20.83 ± 3.50 drop), compared to control (27.21 ± 2.4% and 19.92 ± 1.7%, respectively). PGC also prevented permeability increase in PSE (72.02 ± 26.7 Tn / To) and in PEE (43.88 ± 22.5 Tn / To), compared to the control (194.4 ± 40.2 and 222 , 8 ± 62.9 Tn / To). We conclude that PSE and PEE present differences in the integrity of esophageal mucosa integrity and that the topical application of PGC prevents mucosal changes in PSE biopsies.